Development of Tamarindus indica seed Derived polysaccharide and kaolin complexed Nanosponges for Hemorrhage control - Abinaya, L.; Sudha, R.; Pavithra, M.; Aswitha, K.S. (Journal of Neonatal Surgery, 2025)
Uncontrolled bleeding continues to pose serious challenges in emergency trauma care, requiring the advancement of swift and powerful hemostatic agents. This report study investigated the development and assessment of nanosponges synthesized from Tamarindus indica seed polysaccharide complexed with kaolin, designed to achieve heightened hemostatic efficacy. The natural polysaccharide was extracted and refined, then crosslinked and combined with kaolin particles through the emulsion solvent diffusion method to fabricate porous, biocompatible nanosponges. The addition of kaolin, a recognized clot-promoting agent, enhances platelet activation and coagulation, while the polysaccharide framework offers structural support and biodegradability. Testing characterized the prepared nanosponges using FTIR, SEM, Porosity and swelling studies which providednoteworthy result. In vitro clotting experiments demonstrated considerably reduced clotting time, signifying productive hemostatic potential. HenceTamarindus indica seed polysaccharide-kaolin nanosponges represent a promising, natural-source, cost-effective solution for hemorrhage control which will benefit in clinical setting..